Child and Adolescent Development for Medical Learners: Developmental Perspectives of Emotions and Illness - Florence Eddins-Folensbee; Jason Scott Klein; Sheila Renee Martinez; Roland Wickes Folensbee; Toi Blakely Harris (Association of American Medical Colleges, 2012)
Abstract This module, Developmental Perspectives of Emotions and Illness, discusses the impact of development on a child's understanding and experience of illness. Cognitive developmental influences are emphasized and the concepts of "immanent justice" (the belief that a form of natural justice exists and is the consequence of misdeeds), germ theories, and contagion are illustrated via a video clip interview with a 12 year old girl. Influences on the adaptation of children and adolescents to medical conditions related to onset, etiology, diagnosis, disability/deformity, and prognosis are reviewed and the concept of risk/protective factor is introduced. Additionally, pediatric hospitalization and its influential variables and developmental considerations are highlighted via a video clip interview of two boys (ages 12 and 14) discussing the older boy's hospitalization at age 10. Strategies to maximize coping in the ill child as well as other family members are reviewed. This submission is one of six modules which can be used together as a complete course or independently by topic. Each module uses teaching tools which include learning objectives, lecture outline lecture text, clinical correlations or case vignettes, sample test questions, recent related research, after-class exercises or activities, audiovisual aids including some dedicated teaching clips or transcripts, bibliographies, and PowerPoint presentations. It is not unusual for medical learners to devalue course material deemed "soft science" even when the learner is psychologically sophisticated, particularly when taught concurrent with challenging and volume intensive courses requiring memorization of many details. Such was the case when this course was instituted at a large medical school 15 or more years ago. Because educational leaders felt the material to be essential to the learner's integration of the "biopsychosocial" approach to patient care, and also supported on of the course's tenets (that improved self-understanding and self-reflection supports physician self-care and the doctor-patient relationship), course leaders undertook a process of course examination and improvement which is ongoing. Included in this submission are assessment samples from in-house course evaluations and also from other institutions exposed to the materials that support the success of this curriculum. The authors of this submission believe that the comprehensive course format utilizing a multi-media approach, lectures as well as after-class activities, case correlations, etc. appeals to almost all learners.